2001
DOI: 10.1074/jbc.m108129200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Functional Features of Plant Potassium HvHAK1 and HvHAK2 Transporters

Abstract: Plant K؉ transporters of the HAK family belong to four rather divergent phylogenetic clusters, although most of the transporters belong to clusters I or II. A simple phylogenetic analysis of fungal and plant HAK transporters suggests that an original HAK gene duplicated even before fungi and plants diverged, generating transporters that at present fulfill different functions in the plant. The HvHAK1 transporter belongs to cluster I and mediates high-affinity K ؉ uptake in barley roots, but no function is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 40 publications
2
79
1
Order By: Relevance
“…This result was unexpected because although root tips are comprised of many different cell types, root hairs are of a single cell type. The plethora of AtKT/KUPs expressed in the root hairs may provide indirect support for the suggestion put forward by Senn et al (2001) that the AtKT/ KUPs are localized to different membranes, such as the plasma and tonoplast membrane (Senn et al, 2001;Banuelos et al, 2002). Based on functional data showing a difference in the optimal pH for uptake and phylogenetic groupings, AtKT/HAK/KUPs from both barley (Hordeum vulgare) and rice were also suggested to be localized on the vacuolar membrane.…”
Section: Complementation and Rbmentioning
confidence: 88%
See 3 more Smart Citations
“…This result was unexpected because although root tips are comprised of many different cell types, root hairs are of a single cell type. The plethora of AtKT/KUPs expressed in the root hairs may provide indirect support for the suggestion put forward by Senn et al (2001) that the AtKT/ KUPs are localized to different membranes, such as the plasma and tonoplast membrane (Senn et al, 2001;Banuelos et al, 2002). Based on functional data showing a difference in the optimal pH for uptake and phylogenetic groupings, AtKT/HAK/KUPs from both barley (Hordeum vulgare) and rice were also suggested to be localized on the vacuolar membrane.…”
Section: Complementation and Rbmentioning
confidence: 88%
“…It has been suggested that some of the KT/HAK/KUPs mediate plasma membrane uptake, whereas others are involved in vacuolar transport (Senn et al, 2001). Two studies of AtKT/KUP mutants in Arabidopsis show that mutations cause reduced cell expansion (Rigas et al, 2001;Elumalai et al, 2002).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The translocation of Na + into vacuoles by vacuolarlocalized Na + /H + antiporters, such as At-NHX, provides another mechanism to prevent the toxic accumulation of Na + in the cytoplasm (Apse et al, 1999;Yokoi et al, 2002;Apse et al, 2003;An et al, 2007;Barragán et al, 2012). Voltage-dependent cation channels (HKT and KUP), proton pumps (the H + -ATPase and the H + -pyrophosphatase) and a Ca 2+ /H + antiporter (VCX1) also play roles in Na + compartmentation (Assmann and Haubrick, 1996;Serrano et al, 1999;Gaxiola et al, 2001;Senn et al, 2001;Berthomieu et al, 2003;Rus et al, 2004;Davenport et al, 2007;Fuglsang et al, 2007;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%